2018
DOI: 10.3390/met8110898
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of High-Performance Bi-Metal Bevel Gears by Combined Deposition Welding and Forging

Abstract: The present paper describes a new method concerning the production of hybrid bevel gears using the Tailored Forming technology. The main idea of the Tailored Forming involves the creation of bi-metal workpieces using a joining process prior to the forming step and targeted treatment of the resulting joint by thermo-mechanical processing during the subsequent forming at elevated temperatures. This improves the mechanical and geometrical properties of the joining zone. The aim is to produce components with a hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The use of forging for bi-metal gear production dates back to as early as the 1970s [132]. Studies by Politis et al [118] and Chugreeva et al [38] have demonstrated the production of bi-metal spur gears and bevel gears respectively through forging, with Chavdar et al [32] investigating the principle of hydroforging. In addition, Meißner et al [97] analysed the performance of helical gears manufactured from multi-component forging and layered sheet stapling.…”
Section: Forgingmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of forging for bi-metal gear production dates back to as early as the 1970s [132]. Studies by Politis et al [118] and Chugreeva et al [38] have demonstrated the production of bi-metal spur gears and bevel gears respectively through forging, with Chavdar et al [32] investigating the principle of hydroforging. In addition, Meißner et al [97] analysed the performance of helical gears manufactured from multi-component forging and layered sheet stapling.…”
Section: Forgingmentioning
confidence: 99%
“…Several research works have proposed variants of welding to join dissimilar metals prior to forging. Welding of dissimilar metals may be achieved by metal inert gas welding, submerged arc deposition, plasma-transferred arc [51], c Micrograph of the bond zone before forming, d Micrograph of the bond zone after forming [38] (PTA), laser deposition welding and electro-slag-welding [6]. Chugreeva et al [38] utilised deposition welding to produce a preform for a forged bevel gear manufactured from a cylindrical base material coated with a dissimilar metallic layer.…”
Section: Weldingmentioning
confidence: 99%
“…Behrens et al and Chugreeva et al manufactured hybrid bevel gears using a Tailored Forming process chain [3,4]. Shafts of low alloyed steel C22.8 with a protective cladding of heat treatable steel 41Cr4 were manufactured using a plasma transferred arc (PTA) welding process.…”
Section: Tailored Formingmentioning
confidence: 99%
“…One example are axle shafts, in which the hub is fastened to the axle shaft in the process of frictional butt-welding [18,19]. Studies have also been carried out on plastic forming of two materials during which they are welded to yield a monolithic part characterized by unique physico-chemical properties [20][21][22][23]. It should be noted, however, that in many cases, the process of joining two different materials is relatively expensive and complicated [24,25], and does not guarantee the formation of a permanent joint.…”
Section: Introductionmentioning
confidence: 99%